Polymicrobial prosthetic joint infection: Unusual presentation requiring a multidisciplinary and patient centered approach to treatment - Paul M. Alvarez; Cole Veliky; John McKeon; Douglas Chonko (Journal of Orthopaedic Reports)
We present a case of polymicrobial prosthetic joint infection in a patient with history of left total hip arthroplasty for treatment of avascular necrosis following a femoral neck fracture. Aspiration results from the day of presentation were positive for eight total organisms, including gram-positive and gram-negative bacteria. Successful treatment of this patient's infection required a multidisciplinary approach with assistance from infectious disease, internal medicine and plastic surgery physicians. Treatment included explant with placement of an antibiotic spacer, multiple courses of intravenous antibiotics, vascularized muscle flap and reimplantation with one year of antibiotic suppression. Our case highlights both the importance of a multidisciplinary approach as well as a patient specific approach to treatment when treating patients with prosthetic joint infections.